mid-season crash in aphid populations: why and how does it occur? - Karley, A.J; Parker, W.E; Pitchford, J.W; Douglas, A.E (Ecological entomology, 2004)
1. Aphid populations on agricultural crops in temperature regionscollapse over a few days from peak numbers to local extinction soon after midsummer (e.g. mid-July in the U.K.). The populations recover 6-8 weeks later. There is anecdotal or incidental evidence of an equivalent mid-season population crash of aphids on grasses and forbs in natural vegetation. 2. The ecological factors causing the mid-season population crash of aphids include a decline in plant nutritional quality and increased natural enemy pressure as the season progresses. Extreme weather events, e.g. severe rainstorms, can precipitate the crash but weather conditions are not a consistent contributory factor. 3. The population processes underlying the crash comprise enhanced emigration,especially by alate (winged) aphids, depressed performance resulting in reduced birth rates, and elevated mortality caused by natural enemies.4. Mathematical models, previously applied to aphid populations on agricultural crops, have great potential for studies of aphid dynamics in natural vegetation. In particular, they can help identify the contribution of various ecological factors to the timing of the population crash and offer explanations for how slow changes in population processes can result in a rapid collapse of aphid populations.